Language Proficiency Test In Arabic Language Learning - Amalia Lailatul Muna; Nanang Kosim; Eva Fauziah (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to explore the development of techniques and instruments for language knowledge testing in Arabic language learning. Language tests play a significant role in the evaluation of learning, not only to measure grammar and vocabulary proficiency but also to assess listening, speaking, reading, and writing skills. Based on a literature analysis, this study suggests the application of a more diverse and comprehensive approach to the development of Arabic language tests, taking into account digital technology, access challenges, and relevant teaching needs. This research uses a descriptive qualitative approach with a literature review that analyzes theories and previous studies related to Arabic language evaluation instruments. The main findings show that digital-based assessment instruments, such as online tests and project-based assessments, offer flexibility and efficiency, although challenges related to student honesty and unequal access to technology need to be addressed. The conclusion of this study emphasizes the importance of developing assessment instruments that incorporate cognitive, psychomotor, and affective aspects of students, and recommends introducing digital-based instruments that can be accessed equitably by all students.